The student will be able to:

Slides:



Advertisements
Similar presentations
The student will be able to:
Advertisements

y=3x Find y if x=3 2. Find y if x= -2
Solve by graphing: y = -7x + 2 x + 4y = 8 (0,2). Objective: To use the substitution method to solve systems of linear equations.
4.3 Systems of Equations - Elimination Objective: The student will be able to: Solve systems of equations using elimination with addition and subtraction.
Elimination Using Addition and Subtraction. Solving Systems of Equations So far, we have solved systems using graphing and substitution. Solve the system.
The student will be able to:
Objective The student will be able to: solve systems of equations using substitution. December 3, 2014.
Warm Up What is the opposite of 5? What is the opposite of –2? Distribute 3(x + 2) Distribute –2(x + 4) Distribute –4(x – 3)
Objective The student will be able to: solve systems of equations using elimination with addition and subtraction. SOL: A.9 Designed by Skip Tyler, Varina.
1.2 Solving Linear Systems by Substitution 9/19/12.
Substitution Method: 1. Solve the following system of equations by substitution. Step 1 is already completed. Step 2:Substitute x+3 into 2 nd equation.
Objective The student will be able to: solve systems of equations using substitution. SOL: A.9.
Objective The student will be able to: solve systems of equations using substitution (including special cases in which lines are parallel or coinciding)
5.2: Solving Systems of Equations using Substitution
 What is the slope of the line that passes through the following points. 1.(-2, 5) (1, 4)  Identify the slope and y -intercept of each equation. 2.y.
Objective The student will be able to: solve systems of equations using elimination with addition and subtraction. SOL: A.4e Designed by Skip Tyler, Varina.
Solving Systems of Equations By Substitution – Easier
Solving Linear Systems of Equations by Substitution Section 3.2, Part I.
Solving Systems of Equations So far, we have solved systems using graphing and substitution. These notes show how to solve the system algebraically using.
Objective The student will be able to: solve systems of equations using elimination with addition and subtraction.
7.2 Solving Systems Using Substitution. 7.2 – Solving Syst. By Subst. Goal / “I can…” Solve systems using substitution.
Solving Systems of Equation Using Subsitution Lesson 6-2 Oct. 24, 2014.
The student will be able to:
Objective I can solve systems of equations using elimination with addition and subtraction.
Solving Systems of Equations
Warm Up x = y – 3 9 – 3x 12 9 Simplify each expression.
The student will be able to:
The student will be able to:
Solving Systems of Equations with Substitution
The student will be able to:
Math 1201-Unit:7 Systems of Linear equations
The student will be able to:
Warm up + 4x – 3y = 1 + 9y + 4x = -1 Add the following polynomials 2.
The student will be able to:
The student will be able to:
The student will be able to:
The student will be able to:
SYSTMES OF EQUATIONS SUBSTITUTION.
The student will be able to:
The student will be able to:
The student will be able to:
The student will be able to:
3.2a – Solving Systems algebraically
The student will be able to:
The student will be able to:
The student will be able to:
The student will be able to:
The student will be able to:
Maintenance Sheet 18 Due Tomorrow
The student will be able to:
The student will be able to:
Solving Systems of Equations
Question How do you solve a system of simultaneous equations by substitution?
The student will be able to:
The student will be able to:
Systems of Equations.
Solving Systems of Equations
Warm-Up Solve the system by graphing..
The student will be able to:
The student will be able to:
Solving Systems of Equations
The student will be able to:
Solving Systems by Substitution
The student will be able to:
The student will be able to:
The student will be able to:
The student will be able to:
The student will be able to:
The student will be able to:
The student will be able to:
Presentation transcript:

The student will be able to: Objective The student will be able to: Solve Systems of Equations using substitution. Adapted from Skip Tyler PowerPoint

Solving Systems of Equations You can solve a system of equations using different methods. The idea is to determine which method is easiest for that particular problem. These notes show how to solve the system algebraically using SUBSTITUTION. You will usually use this method mostly when one of your equations is ALREADY solved for a variable, or easily solved for a variable with one transformation.

Solving a system of equations by substitution Step 1: Solve an equation for one variable. Pick the easier equation. The goal is to get y= ; x= ; a= ; etc. Step 2: Substitute Substitute the equation solved in Step 1 into the other equation. Step 3: Solve the equation. Get the variable by itself. Step 4: Plug back in to find the other variable. Substitute your answer back into the equation to find other value. Step 5: Check your solution. Substitute ordered pair (solution you just found) into BOTH equations.

1) Solve the system using substitution(EASY) x + y = 5 y = 3 + x Step 1: Solve an equation for one variable. The second equation is already solved for y! Step 2: Substitute x + y = 5 becomes x + (3 + x) = 5 2x + 3 = 5 2x = 2 x = 1 Step 3: Solve the equation.

1) Solve the system using substitution(EASY) x + y = 5 y = 3 + x Remember, we just found that x = 1 x + y = 5 (1) + y = 5 y = 4 Step 4: Substitute back in to find the other variable. (1, 4) (1) + (4) = 5 (4) = 3 + (1) Step 5: Check your solution. The solution is (1, 4). What do you think the answer would be if you graphed the two equations?

1) Solve the system using substitution(EASY) Try it before you click for answer. You ONLY get better by practicing problems. HINT: Put 6 + y in for x 1) Solve the system using substitution(EASY) 3x + 3y = 6 x = 6 + y Step 1: Solve an equation for one variable. The second equation is already solved for x! Step 2: Substitute 3x + 3y = 6 becomes 3(6+y)+ 3y = 6 18 + 3y + 3y = 6 18 + 6y = 6 6y = -12 y = -2 Step 3: Solve the equation.

1) Solve the system using substitution(EASY) 3x + 3y = 6 x = 6+ y We found y= -2 in previous step. x= 6+y x= 6 + (-2) x = 4 , solution ( 4, -2) Step 4: Plug back into easiest equation to find the other variable. (4, -2) 3(4) + 3(-2) = 6 (4) = 6 + (-2) Step 5: Check your solution into each equation. The solution is (4, -2). What do you think the answer would be if you graphed the two equations?

Which answer checks correctly? Try it before you click for answer. You ONLY get better by practicing problems. HINT: Put 4y-17 in for x Which answer checks correctly? 3(4y - 17) –y = 4 12y- 51 - y = 4 11y = 55 , y = 5 Substitute 5 in for y in one of the equations to find x. x = 4(5) -17 >>> x = 20-17 =3 Solution: (3, 5) 3x – y = 4 x = 4y - 17 (2, 2) (5, 3) (3, 5) (3, -5)

Which answer checks correctly? Try it before you click for answer. You ONLY get better by practicing problems. HINT: Put 4x-4 in for y Which answer checks correctly? 2x + 2(4x - 4) = 12 2x + 8x -8 = 12 10x = 20 , x = 2 Substitute 2 in for x in one of the equations to find y. y = 4(2) -4 >>> y = 8 - 4 = 4 Solution: (2, 4) 2x + 2y = 12 y = 4x - 4 (2, 4) (4, 2) (-2, -4) (-4, -2)

2) Solve the system using substitution 3y + x = 7 4x – 2y = 0 Step 1: Solve an equation for one Variable (get x or y by itself). Choose the equation that will transform the easiest. It is easiest to solve the first equation for x. 3y + x = 7 -3y -3y x = -3y + 7 Step 2: Substitute 4x – 2y = 0 becomes 4(-3y + 7) – 2y = 0

2) Solve the system using substitution Remember, we were here 4(-3y + 7) – 2y = 0 3y + x = 7 4x – 2y = 0 -12y + 28 – 2y = 0 -14y + 28 = 0 -14y = -28 y = 2 Step 3: Solve the equation. 4x – 2y = 0 4x – 2(2) = 0 4x – 4 = 0 4x = 4 x = 1 Step 4: Substitute back in to find the other variable. (Either equation, doesn’t matter)

2) Solve the system using substitution 3y + x = 7 4x – 2y = 0 Step 5: Check your solution. (1, 2) 3(2) + (1) = 7 4(1) – 2(2) = 0 When is solving systems by substitution easier to do than graphing? When only one of the equations has a variable already isolated (like in example #1).

2x + 4y = 4 3x + 2y = 22 -4y + 4 -2y + 2 -2x + 4 -2y+ 22 If you solved the first equation for x, what would be substituted into the bottom equation. 2x + 4y = 4 -4y = -4y 2x = -4y + 4 2 2 x = -2y + 2 2x + 4y = 4 3x + 2y = 22 -4y + 4 -2y + 2 -2x + 4 -2y+ 22

Solve the system using substitution. Special Case #1 x = 3 – y x + y = 7 Step 1: Solve an equation for one variable. The first equation is already solved for x! Step 2: Substitute x + y = 7 (3 – y) + y = 7 3 = 7 The variables were eliminated!! This is a special case. Does 3 = 7? FALSE! Step 3: Solve the equation. When the result is FALSE, the answer is NO SOLUTIONS.

Solve the system using substitution Special Case #2 2x + y = 4 4x + 2y = 8 Step 1: Solve an equation for one variable. The first equation is easiest to solved for y! y = -2x + 4 4x + 2y = 8 4x + 2(-2x + 4) = 8 Step 2: Substitute 4x – 4x + 8 = 8 8 = 8 This is also a special case. Does 8 = 8? TRUE! Step 3: Solve the equation. When the result is TRUE, the answer is INFINITELY MANY SOLUTIONS.